Pengaruh Endorphin Massage Terhadap Intensitas Nyeri Punggung Pada Ibu Hamil Trimester III: Systematic Review - Mardliyana, Nova Elok; Agustin, Della; Maya Puspita, Irma (Universitas Muhammadiyah Surabaya, 2024)
Objective: Back pain is an uncomfortable feeling that pregnant women often experience during the third trimester. The centre of gravity influences the enlargement of the uterus, which stretches outward. Not only that, weakening of the abdominal muscles, changes in body position, and pressure on the back are also influenced by the centre of gravity in the mother's stomach. As a result, the pregnant woman's back will be pulled backwards, and the pregnant woman will arch her neck. This posture causes the lower back to curve and pulls the back muscles, causing pain. Endorphin massage is a massage that stimulates the body to generate endorphin compounds as pain relievers. The research aims to understand and determine the effect of endorphin massage on the intensity of back pain in third-trimester pregnant women. Methods: The method used in this research is the systematic literature review method using the Google Scholar and Research database. The procedure for collecting articles is from quantitative research journals from the last ten years & has a minimum index of Sinta 5. Articles from research journals are searched using the keywords